The Risk of Decubitus Ulcers in Bed Rest Patients in The Intensive Care Unit - Khoironi, Rahmi; Basri, Ahmad Hasan; Laily, Nurul Fahmi Rizka (Jurnal Surya, 2025)
Introduction: Bed rest patients are at high risk of developing decubitus ulcers, which can increase morbidity and mortality. Mobilization every two hours is primary prevention, but is often overlooked due to nurses' workload. The Matras Mob was developed to facilitate optimal patient mobilization. This study analyzed the effect of the Matras Mob intervention on the risk of developing decubitus ulcers in ICU patients. Methods: Using a pre-experimental one-group pre-posttest design, this study involved 33 respondents with total sampling. Data was collected using the Braden Scale before and three days after the intervention, then analyzed with the Wilcoxon Signed Ranks Test. Results: Results showed a significant difference in decubitus ulcer risk before and after the intervention (p = 0.000). Before the intervention, the majority of patients were at very high risk, while afterward the risk decreased to high and low. Conclusion: Matras Mob is effective in reducing the risk of decubitus ulcers and is recommended as an innovation in the prevention of decubitus ulcers in bed rest patients in the ICU. Keywords: Bed Rest, Decubitus Ulcer, ICU, Matras Mob, Mobilization